1770. Effects of Acculturation and Social Norms on Intention to use Antibiotics without a Prescription among Hispanic or Latino individuals. (15th December 2022) - Alquicira, Osvaldo; Trautner, Barbara; Raphael, Jean; Salinas, Juanita; Barning, Kenneth; Mahmood, Hammad; Porter, Thomas; Street, Richard; Lopez-Alonso, Moramay; Paasche-Orlow, Michael K; Grigoryan, Larissa
Abstract: Background: The use of antibiotics obtained without a prescription (non-prescription use) in the United States (U.S.) may contribute to antimicrobial resistance. We hypothesized that among Hispanic/Latino patients, the intention to use non-prescription antibiotics would be associated with: [1] lower acculturation (preference to socialize with Hispanic/Latinos) and [2] having friends or relatives who use antibiotics without contacting a doctor (social norms). Methods: We conducted a survey on the factors that impact Hispanic/Latino patients' decisions to use non-prescription antibiotics in safety-net primary care clinics and private emergency departments in the greater Houston, Texas area between January 2020 and June 2021. Surveys were read to patients in English or Spanish and queried patient, health system, and clinical encounter factors. Results: Of 263 Hispanic/Latino patients, 59% completed the survey in Spanish and 41% in English (Table 1). Overall, 47% reported previous non-prescription antibiotic use, and 36% professed intention to hypothetically obtain and use non-prescription antibiotics, if feeling sick, from one or more of three sources (bought without a prescription in the U. S., from another country, and from friends or relatives). Lack of health insurance, being surveyed in Spanish, having friends or relatives who use antibiotics without consulting a doctor, and high cost of doctor visits were predictors of intent to use antibiotics bought without a prescription in the U.S. (Table 2). Predictors of intent to use non-prescription antibiotics from other countries included lower acculturation scores (preferring to socialize with Hispanics/Latinos), younger age, having friends or relatives who use antibiotics without consulting a doctor, and reported language barriers to medical appointments. Predictors of intent to use antibiotics from friends and relatives included having friends or relatives who use antibiotics without consulting a doctor, and high cost of doctor visits. Conclusion: Interventions aimed at reducing non-prescription use in the Hispanic/Latino community should focus on ensuring affordable language concordant healthcare and promoting antibiotic stewardship as a social norm. Disclosures: Barbara Trautner, MD, PhD, Genetech: Advisor/Consultant Michael K. Paasche-Orlow, MD, MPH, GlaxoSmithKline: Advisor/Consultant Larissa Grigoryan, MD, PhD, Rebiotix Inc: Grant/Research Support.